2013
DOI: 10.4236/ojce.2013.33b001
|View full text |Cite
|
Sign up to set email alerts
|

Significance Analysis of Flexural Behaviour of Hybrid Sandwich Panels

Abstract: This paper presents the significance analysis of a new type of hybrid composite sandwich wall panel which can be manufactured as modular panelised system. Two different types of natural fibers reinforced plastics (NFRP) laminate were incorporated into the new sandwich panel as an intermediate layer. The significance analysis in this research has been carried out using analysis of variance (ANOVA). As the aim of the analysis is to select the most appropriate natural fiber composites for the intermediate layer, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 7 publications
1
8
0
Order By: Relevance
“…An experimental investigation with different wood based materials for the intermediate layer in smallscale samples was conducted by Fajrin et al [2] and the results confirmed the claim of the previous study [1]. A further investigation with statistical design of experiment approach has also confirmed the significant impovement achieved by the introduction of the intermediate layer [3]. It was found that intermediate layer made of jute fiber composite and medium density fiber improved the structural performance of the hybrid sandwich panel.…”
Section: Introductionsupporting
confidence: 68%
“…An experimental investigation with different wood based materials for the intermediate layer in smallscale samples was conducted by Fajrin et al [2] and the results confirmed the claim of the previous study [1]. A further investigation with statistical design of experiment approach has also confirmed the significant impovement achieved by the introduction of the intermediate layer [3]. It was found that intermediate layer made of jute fiber composite and medium density fiber improved the structural performance of the hybrid sandwich panel.…”
Section: Introductionsupporting
confidence: 68%
“…Research into the feasibility of reinforcing epoxy or polyester with natural fibers has been reported in several literature [31][32][33][34]. A comprehensive theoretical framework for the new sandwich structure panel developed in this research under flexural loading was thoroughly discussed [35], while the statistical analysis of the flexural test was reported earlier [36]. More recently, a statistical analysis of the in-plane shear behaviour of the newly developed panel was also reported [37].…”
Section: Introductionmentioning
confidence: 99%
“…A hybrid sandwich panel that is formed by inserting intermediate layer between skins and core has shown excellent performance under flexural loading as reported by Fajrin et al [1,2]. The concept of hybrid sandwich panel with intermediate layer itself was first developed by Mamalis et al [3].…”
Section: Introductionmentioning
confidence: 93%